2016
DOI: 10.4155/fmc.15.182
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Bacterial and Fungal Pathogens by the Orphaned Drug Auranofin

Abstract: Background:We identified auranofin as an antimicrobial compound utilizing a highthroughput screen using a Caenorhabditis elegans-Staphylococcus aureus infection model. Results/methodology: Treatment of infected nematodes with auranofin resulted in a prolonged survival rate of 95%, reached with 0.78 μg/ml. Further investigation of the antimicrobial activity of auranofin found inhibition against S. aureus, Enterococcus faecium and Enterococcus faecalis. Importantly, the fungal pathogens Cryptococcus neoformans w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
60
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 38 publications
5
60
0
Order By: Relevance
“…Recent studies, including the present work, demonstrate that auranofin inhibits the planktonic growth of multiple species of fungi including C. albicans, C. glabrata, C. tropicalis, C. parapsilosis, C. neoformans , and C. gattii with an average MIC of 4 μg/ml (Stylianou et al, 2014; Fuchs et al, 2016). …”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Recent studies, including the present work, demonstrate that auranofin inhibits the planktonic growth of multiple species of fungi including C. albicans, C. glabrata, C. tropicalis, C. parapsilosis, C. neoformans , and C. gattii with an average MIC of 4 μg/ml (Stylianou et al, 2014; Fuchs et al, 2016). …”
Section: Discussionsupporting
confidence: 51%
“…Recent studies by Fuchs et al (2016) and Stylianou et al (2014) reported that auranofin also possesses antifungal activity. However, the antifungal MOA and in vivo antifungal efficacy of auranofin remain unclear with several possible targets reported.…”
Section: Introductionmentioning
confidence: 99%
“…57 Likewise, recombinant CaTrxR protein induced high levels of serum specific antibodies and reduced the fungal burden in experimental disseminated candidiasis in mice. 58 In addition, recent studies on the thioredoxin reductase inhibitor auranofin 59 highlighted its promising antimicrobial potential against various bacteria, [60][61][62][63] as well as some pathogenic yeasts 61,64 and filamentous fungi. 64 Finally, our experiments also showed overexpression of the flavohemoglobin gene SAPIO CDS8682 and the nitrite reductase gene SAPIO CDS10292 upon exposure to DETA-NO.…”
Section: Discussionmentioning
confidence: 99%
“…Our focus in one of these targets, TRR1, has already resulted in the discovery of new small molecule antifungal candidates (Abadio et al, 2015). TRR1 might also be a target for auranofin, an antirheumatic drug that displayed interesting properties in studies that aimed to repurpose it as an antifungal (Siles et al, 2013;Fuchs et al, 2016;Thangamani et al, 2017;Wiederhold et al, 2017). In this work we made the first steps in validating this target for antibody-based therapies as well.…”
Section: Discussionmentioning
confidence: 99%